Latin America: A Development Pole for Phenomics - Camargo, Anyela V.; Lobos, Gustavo A. (Frontiers in Plant Science, 2016)
Latin America and the Caribbean (LAC) has long been associated with the production and export of a diverse range of agricultural commodities. Due to its strategic geographic location, which encompasses a wide range of climates, it is possible to produce almost any crop. The climate diversity in LAC is a major factor in its agricultural potential but this also means climate change represents a real threat to the region. Therefore, LAC farming must prepare and quickly adapt to a climate that is likely to feature long periods of drought, excessive rainfall and extreme temperatures. With the aim of moving towards a more resilient agriculture, LAC scientists have created the Latin American Plant Phenomics Network (LatPPN) which focuses on LAC’s economically important crops. LatPPN’s key strategies to achieve its main goal are: 1) training of LAC members on plant phenomics and phenotyping, 2) establish international and multidisciplinary collaborations, 3) develop standards for data exchange and research protocols, 4) share equipment and infrastructure, 5) disseminate data and research results, 6) identify funding opportunities and 7) develop strategies to guarantee LatPPN’s relevance and sustainability across time. Despite the challenges ahead, LatPPN represents a big step forward towards the consolidation of a common mind-set in the field of plant phenotyping and phenomics in LAC.